2021
DOI: 10.1007/s10529-021-03104-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of the carbon catabolite repressor CreA leads to low but inducer‐independent expression from the feruloyl esterase B promoter in Aspergillus niger

Abstract: Objective With the aim to decipher the mechanisms involved in the transcriptional regulation of feruloyl esterase encoded by faeB, a genetic screen was performed to isolate A. niger mutants displaying inducer-independent expression from the faeB promoter. Result PfaeB-amdS and PfaeB-lux dual reporter strains were constructed and used to isolate trans-acting mutants in which the expression of both reporters was increased, based on the ability to grow on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…The A. niger strains used in this study are listed in Table 1. A. niger strain JR11.1 contains two reporter genes (PfaeB-amdS and PfaeB-lux 613) to monitor the activity of the faeB promoter via the ability to grow on acetamide plates or via luciferase assay (Reijngoud et al, 2021). Strains were grown on liquid or solidified (containing 1.5% (w/v) Scharlau agar (Scharlau, Barcelona, Spain)) minimal medium (MM) or on complete medium (CM) MM contains 7 mM KCl, 8 mM KH 2 PO 4 , 70 mM NaNO 3 , and 2 mM MgSO 4 (pH adjusted to 5.5) and spore elements as described (Arentshorst et al, 2012).…”
Section: Strains Media and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The A. niger strains used in this study are listed in Table 1. A. niger strain JR11.1 contains two reporter genes (PfaeB-amdS and PfaeB-lux 613) to monitor the activity of the faeB promoter via the ability to grow on acetamide plates or via luciferase assay (Reijngoud et al, 2021). Strains were grown on liquid or solidified (containing 1.5% (w/v) Scharlau agar (Scharlau, Barcelona, Spain)) minimal medium (MM) or on complete medium (CM) MM contains 7 mM KCl, 8 mM KH 2 PO 4 , 70 mM NaNO 3 , and 2 mM MgSO 4 (pH adjusted to 5.5) and spore elements as described (Arentshorst et al, 2012).…”
Section: Strains Media and Growth Conditionsmentioning
confidence: 99%
“…Several ferulyol esterases (FaeA-D) have been identified in A. niger , with expression of the genes being induced only under specific conditions. FaeA expression is induced on xylose, arabinose and several aromatics, whereas FaeB expression is only induced on aromatics ( de Vries et al., 2002 ; Reijngoud et al., 2021 ). FaeC is generally lowly expressed ( Dilokpimol et al., 2017 ; Oliveira et al., 2019 ; Lubbers et al., 2020 ) and no data are currently available for FaeD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During fungal growth in both the natural niche and industrial bioprocesses, glucose is the preferred sugar over other carbon sources, which leads to the inactivation of the transport and metabolic pathway involved in the assimilation of alternative carbon sources. This preference was known as carbon catabolite repression (CCR) ( Reijngoud et al, 2021 ), resulting in the repression of catabolizing other alternative carbon sources until glucose was depleted ( Makela et al, 2018 ). In many filamentous fungi, the transcription repressor CreA is considered to be the major component of CCR, and its function and stability are regulated in response to glucose ( Reijngoud et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This preference was known as carbon catabolite repression (CCR) ( Reijngoud et al, 2021 ), resulting in the repression of catabolizing other alternative carbon sources until glucose was depleted ( Makela et al, 2018 ). In many filamentous fungi, the transcription repressor CreA is considered to be the major component of CCR, and its function and stability are regulated in response to glucose ( Reijngoud et al, 2021 ). Interestingly, however, Mäkelä et al found that A. niger takes up monomeric sugars in a sequential manner which is not mediated by CreA in some instances ( Makela et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%